Cancer multicellular spheroids: Volume assessment from a single 2D projection. Issue 2 (February 2015) - Piccinini, Filippo; Tesei, Anna; Arienti, Chiara; Bevilacqua, Alessandro
Highlights We present a new image-based approach to compute multicellular spheroid volume. The reconstruction method is validated by using home-made 3D objects. A new strategy to compare different volume estimation methods is discussed. The results obtained by ReViSP overcome those of the other methods tested. ReViSP source code and standalone executable version are freely available.